Complete revascularization for patients with ST-segment elevation myocardial infarction and multivessel coronary artery disease: a meta-analysis of randomized trials. Issue 3 (May 2018) - Bajraktari, Gani; Jashari, Haki; Ibrahimi, Pranvera; Alfonso, Fernando; Jashari, Fisnik; Ndrepepa, Gjin; Elezi, Shpend; Henein, Michael Y.
Abstract : Introduction: Despite the recent findings in randomized clinical trials (RCTs) with limited sample sizes and the updates in clinical guidelines, the current available data for the complete revascularization (CR) in hemodynamically stable patients with ST-segment elevation myocardial infarction (STEMI) at the time of primary percutaneous coronary intervention (PCI) are still contradictory. Aim: The aim of this meta-analysis of the existing RCTs was to assess the efficacy of the CR versus revascularization of infarct-related artery (IRA) only during primary PCI in patients with STEMI and multivessel disease (MVD). Patients and methods: We searched PubMed, MEDLINE, Embase, Scopus, Google Scholar, Cochrane Central Register of Controlled Trials (CENTRAL), and ClinicalTrials.gov databases aiming to find RCTs for patients with STEMI and MVD which compared CR with IRA-only. Random effect risk ratios (RRs) were calculated for efficacy and safety outcomes. Results: Ten RCTs with 3291 patients were included. The median follow-up duration was 17.5 months. Major adverse cardiac events (RR=0.57; 0.43–0.76; P <0.0001), cardiac mortality (RR=0.52; 0.31–0.87; P =0.014), and repeat revascularization (RR=0.50; 0.30–0.84; P =0.009) were lower in CR compared with IRA-only strategies. However, there was no significant difference in the risk of all-cause mortality, recurrent nonfatal myocardial infarction, stroke, major bleeding events, and contrast-induced nephropathy. Conclusion: For patients with STEMI and MVD undergoing primary PCI, the current evidence suggests that the risk of major adverse cardiac events, repeat revascularization, and cardiac death is reduced by CR. However, the risk for all-cause mortality and PCI-related complications is not different from the isolated culprit lesion-only treatment. Although these findings support the cardiac mortality and safety benefit of CR in stable STEMI, further large trials are required to provide better guidance for optimum management of such patients. Abstract : Supplemental Digital Content is available in the text.